BAP1 promotes the repair of UV-induced DNA damage via PARP1-mediated recruitment to damage sites and control of activity and stability - Lee, Shin-Ai; Lee, Daye; Kang, Minhwa; Kim, Sora; Kwon, Su-Jung; Lee, Han-Sae; Seo, Hye-Ran; Kaushal, Prashant; Lee, Nam Soo; Kim, Hongtae; Lee, Cheolju; Kwon, Jongbum (Nature Publishing Group, 2022)
BRCA1-associated protein-1 (BAP1) is a ubiquitin C-terminal hydrolase domain-containing deubiquitinase with tumor suppressor activity. The gene encoding BAP1 is mutated in various human cancers, with particularly high frequency in kidney and skin cancers, and BAP1 is involved in many cancer-related cellular functions, such as DNA repair and genome stability. Although BAP1 stimulates DNA double-strand break repair, whether it functions in nucleotide excision repair (NER) is unknown. Here, we show that BAP1 promotes the repair of ultraviolet (UV)-induced DNA damage via its deubiquitination activity in various cell types, including primary melanocytes. Poly(ADP-ribose) polymerase 1 (PARP1) interacts with and recruits BAP1 to damage sites, with BAP1 recruitment peaking after the DDB2 and XPC damage sensors. BAP1 recruitment also requires histone H2A monoubiquitinated at Lys119, which accumulates at damage sites. PARP1 transiently poly(ADP-ribosyl)ates (PARylates) BAP1 at multiple sites after UV damage and stimulates the deubiquitination activity of BAP1 both intrinsically and via PARylation. PARP1 also promotes BAP1 stability via crosstalk between PARylation and ubiquitination. Many PARylation sites in BAP1 are mutated in various human cancers, among which the glutamic acid (Glu) residue at position 31, with particularly frequent mutation in kidney cancer, plays a critical role in BAP1 stabilization and promotes UV-induced DNA damage repair. Glu31 also participates in reducing the viability of kidney cancer cells. This study therefore reveals that BAP1 functions in the NER pathway and that PARP1 plays a role as a novel factor that regulates BAP1 enzymatic activity, protein stability, and recruitment to damage sites. This activity of BAP1 in NER, along with its cancer cell viability-reducing activity, may account for its tumor suppressor function.